2016
DOI: 10.1016/j.jadohealth.2015.10.253
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Susceptibility to Peer Influence in Sexual Situations

Abstract: Purpose One consistent predictor of adolescents’ engagement in sexual risk behavior is their belief that peers are engaging in similar behavior; however, not all youth are equally susceptible to these peer influence effects. Understanding individual differences in susceptibility to peer influence is critical to identifying adolescents at risk for negative health outcomes. The purpose of this project was to identify predictors of susceptibility to peer influence using a novel performance-based measure of sexual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
73
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(81 citation statements)
references
References 28 publications
(67 reference statements)
6
73
0
2
Order By: Relevance
“…Male engagement in sexual risk behaviors could result from peer pressure to have sexual intercourse, as this is considered normal for male adolescents (Tipwareerom, Powwattana, & Lapvongwatana, ; Widman, Choukas‐Bradley, Helms, & Prinstein, ), and cultural norms that encourage males to have sexual freedom (Lefkowitz, Shearer, Gillen, & Espinosa‐Hernandez, ). Our findings also revealed that parents were not strongly involved in monitoring the behaviors of their male children and allowed them to engage in sexual relationships, while they more closely monitored the sexual behavior of female children.…”
Section: Discussionmentioning
confidence: 99%
“…Male engagement in sexual risk behaviors could result from peer pressure to have sexual intercourse, as this is considered normal for male adolescents (Tipwareerom, Powwattana, & Lapvongwatana, ; Widman, Choukas‐Bradley, Helms, & Prinstein, ), and cultural norms that encourage males to have sexual freedom (Lefkowitz, Shearer, Gillen, & Espinosa‐Hernandez, ). Our findings also revealed that parents were not strongly involved in monitoring the behaviors of their male children and allowed them to engage in sexual relationships, while they more closely monitored the sexual behavior of female children.…”
Section: Discussionmentioning
confidence: 99%
“…However, the peer context also plays an important role in the initiation and maintenance of a range of risky behaviors and negative outcomes, including substance use, obesity, suicidal behaviors, and increased number of sex partners (Abrutyn and Mueller, 2014; Ali and Dwyer, 2011; Bauman and Ennett, 1994; Faris and Ennett, 2012). The strength of the influence of peer ties vary according to network characteristics such as size (Faris and Ennett, 2012), and individual characteristics such as gender (Widman et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Peer pressure and coercion to sexual activity are a challenge to them despite the availability of adolescent health programmes (Widman et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…Adolescents engage in unplanned, unprotected and early sex as a result of peer pressure and coercion thus increasing their vulnerability to unplanned pregnancies and sexual transmitted infections (STIs; Setswe et al 2014). Peer pressure and coercion to sexual activity are a challenge to them despite the availability of adolescent health programmes (Widman et al 2016).…”
Section: Introductionmentioning
confidence: 99%